Description of a new species of Typhinellus (Gastropoda: Muricidae: Typhinae) from the Western Atlantic - Houart, Roland (Zootaxa, 2015)
There are seven known living species of Typhinellus. Five species occur in the Indo-West Pacific: T. amoenus Houart, 1994 ranges from Natal, South Africa to Somalia with other records off Quissico, southern Mozambique (MNHN); T. androyensis Bozzetti, 2007, described from south Madagascar and also present in the Gulf of Aden (RH coll.); T. bicolor Bozzetti, 2007 described from and presently restricted to southern Madagascar; T. insolitus Houart, 1991 from the Loyalty Ridge and T. occlusus (Garrard, 1963) described from Queensland, Australia and also recorded from southern Philippine Islands. A single species, Typhinellus labiatus (Cristofori & Jan, 1832), occurs throughout the Mediterranean and off the Atlantic coasts of Morocco and southern Spain (Houart, 2001). This species was also recorded from the Canary Islands (Nordsieck & Garcia Talavera, 1979) and off Dakar, Senegal (MNHN and Marche Marchad, 1958). The specimen recorded from the Gulf of Oman in Houart (2001: 114) turned out to be T. androyensis (see above) while the one from Somalia, also in Houart (2001: 114) probably also refers to this species. Another species, Typhinellus lamyi Garrigues & Merle, 2014, was recently described from Guadeloupe. It seems that only one fossil species, T. chipolanus (Gertman, 1969) from late lower Miocene (Burdigalian) of Florida occurs in the Western Atlantic. Two additional species will be described from south Madagascar (Houart & Héros, in press).